Books received. (Journal of Spanish Cultural Studies, 2002)
Features several books received for review in the periodical 'Journal of Spanish Cultural Studies.' 'Deadly Embrace: Morocco and the Road to the Spanish Civil War,' by Sebastian Balfour; 'Charting Memory: Recalling Medieval Spain,' edited by Stacy N. Beckwith; 'Encounters Across Borders: 'The Changing Visions of Spanish Modernism, 1890-1930,' by Mary Lee Bretz; 'British Women and the Spanish Civil War,' by Angela Jackson.